Role of Pharmacists and Nurses to Avoid Physicochemical Drug Interactions to Ensure Patient Safety (Asian Journal of Pharmaceutics (AJP), 2024)
Healthcare professionals such as nurses and pharmacists play a vital role in patient care. The paper underscoresthe roles of nurses and pharmacists in reducing physicochemical drug interaction and improving patient safetythereby improving the overall healthcare system. A comprehensive literature analysis was done to investigate theimpact of physicochemical drug interactions, the responsibilities of nurses and pharmacists in minimizing theseinteractions, and the value of multidisciplinary teamwork. The study also contains therapeutic recommendationsfor avoiding drug-drug, drug-food, and drug-nutrient interactions. There has been an increasing rate of medicationerror due to the physicochemical interaction of the drugs. The unexpected side effects during patient treatmentare particularly concerning, as they can elevate mortality and morbidity rates while driving up therapeutic costs.The data show that approximately 50% of pharmaceutical mistakes are caused by physicochemical interactions,particularly in intravenous dose forms. Nurses and pharmacists can work together to prevent these errors bychecking medication compatibility, continuously monitoring patient reactions, and revising compatibilityrecommendations. As a team, pharmacists can examine prescriptions to avoid contraindicated drug combinations,while nurses, as frontline caretakers, ensure that drugs are administered correctly and the food administered to thepatient does not negatively interact with the medications. Both experts must work together to discover and avoidphysicochemical incompatibilities, which improves patient safety and lowers healthcare costs. This coordinatedapproach is critical for reducing prescription mistakes while improving the overall stability and efficacy ofpharmacological formulations in patient care.